2021
DOI: 10.3390/su13010412
|View full text |Cite
|
Sign up to set email alerts
|

Delineating an Integrated Ecological and Cultural Corridor Network: A Case Study in Beijing, China

Abstract: This study shows that an integrated ecological and cultural corridor network can help guide city development strategies to better preserve ecological and cultural assets. Traditionally, protection zones and suitable development areas are often identified by separately considering natural elements of the ecosystem and elements of cultural significance. To achieve the purpose of cohesively protecting areas of ecological and/or cultural significance, we have developed a corridor-based spatial framework by integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…Through integrating ECR into ecological network construction, this study developed an ecological network system that prioritized the positive effect factors of ECR areas. Compared with the research reported by Li et al (2021), the coverage of ecological corridors in the present study was greater, and ecological flows between patches in the southeast corner of Beijing were identified. The ecological flow between the ECR areas in Beijing was greater in the north-south direction than in the east-west direction.…”
Section: Identifying the Ecological Corridors From The Beijing Ecr To...contrasting
confidence: 97%
“…Through integrating ECR into ecological network construction, this study developed an ecological network system that prioritized the positive effect factors of ECR areas. Compared with the research reported by Li et al (2021), the coverage of ecological corridors in the present study was greater, and ecological flows between patches in the southeast corner of Beijing were identified. The ecological flow between the ECR areas in Beijing was greater in the north-south direction than in the east-west direction.…”
Section: Identifying the Ecological Corridors From The Beijing Ecr To...contrasting
confidence: 97%
“…Secondly, based on the data of land-use types, roads, water systems, landform and geomorphic conditions, the ecological and recreational resistance surfaces are constructed, respectively, and the resistance surfaces integrating multiple elements can make the expression of ecological process closer to the real space [34]. Finally, the ecological and recreational corridors are identified based on the MCR model, and the comprehensive expression of spatial development, protection and utilization is realized by the compound landscape corridor [35] (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The resistance surface refers to the carrier of the obstructed degree of species migration in the corridor, and its construction principle is constructed by calculating the cost of material flow, energy flow and information flow spreading among different landscape patches under the action of various resistance elements [29]. Relevant studies usually adopt land-use type data and set different resistance coefficients for different land-use types, such as forestland, water systems and other green space resistance coefficients, which take the minimum value, and construction land and other land-use types, which take the maximum value [34,35]. Therefore, the method of using land-use type as a dominant factor in the resistance surface, and using road classification, water and terrain factors as auxiliary correction, was completed by referencing the relevant literature to determine the assignment of elements.…”
Section: Construction Of the Resistance Surfacementioning
confidence: 99%
“…As the wide distribution of ancient roads is a characteristic of the Shaanxi Province, appropriate connections with ecological corridors ought to be taken into account when developing and constructing cultural corridors. At present, although there is no systematic methodological framework for combining an ecological corridor with a cultural corridor [37], some researchers have made useful explorations into the construction of integrated ecological and cultural corridors or traditional settlements [18,37,38]. Yu et al (2009) proposed a cultural heritage security pattern based on cultural heritage protection and recreation in Beijing [34].…”
Section: Conflicts Between Human Activities and Ecological Security P...mentioning
confidence: 99%